Penerapan Relaksasi Genggam Jari Terhadap Nyeri pada Pasien Pasca Operasi Sectio Caesarea di Kelurahan Pucangsawit - Desi Nurhidayah; Ika Silvitasari (Lembaga Pengembangan Kinerja Dosen, 2024)
Based on Riskesdas, the rate of cesarean delivery in Indonesia is 20-25% in government hospitals and 30-38% in private hospitals. Sectio Caesarea section is a non-surgical procedure that will injure tissue, so the mother's complaint after caesarean section surgery is pain. One of the non-pharmacological pain management is finger grip relaxation to describe the results of pain scale measurements with finger grip relaxation This application uses a case study method with a descriptive design and uses a Numeric Rating Scale (NRS) pain measurement sheet, carried out for 30 minutes and for 2 days After the application was carried out on 2 respondents, there was a decrease in the pain scale, Mrs. A from a scale of 4 to 3 and Mrs. D from a pain scale of 5 to 3 including the mild category. Finger grip relaxation has an effect on reducing pain scale in patients after sectio caesarean section